Increasing productivity and profit through health and safety: the financial returns from a safe working environment - Oxenburgh, Maurice; Marlow, Pepe; Oxenburgh, Andrew (Boca Raton, FL, 2004)
"The book is designed around human resource strategies, illustrated through case studies, which explain the effectiveness of ergonomics on productivity and profit, both for the employees (a safer and more congenial working environment) and the enterprises (better return on investment). The free software that accompanies this book is a versatile programme for the reader to use in their workplace. In an easy to follow, step-by-step process, the user is asked to enter workplace details and the proposed intervention cost and the programme will calculate the obtained savings and pay-back period. Also included with the software are many of the worked examples from the case studies."